Endoscopic surveillance for colorectal cancer and its precursor lesions in Lynch syndrome; time for some policy shifts? - Romy N Kuipers; Marissa F Burggraaff; Michiel HJ Maas; Dorien TJ van der Biessen – van Beek; Mariëtte CA van Kouwen; Tanya M Bisseling (Hereditary Cancer in Clinical Practice, 2025)
Abstract Background While numerous studies have demonstrated variations in colorectal cancer (CRC) incidence among Lynch Syndrome (LS)-associated germline pathogenic variant (gPV) carriers, limited data are available regarding tailoring surveillance and treatment strategies. The main goal of this study was to estimate whether personalised care could be offered based on the different gPVs (MLH1, MSH2, MSH6 or PMS2). Additionally, the outcome from patient-shared care for early (T1) CRC was investigated. Methods The study is performed as a single centre retrospective analysis of our cohort of patients with a LS-associated gPV in MLH1, MSH2, MSH6 or PMS2. Colon surveillance data from between January 1978 to February 2024 were collected. Analyses were performed to identify differences in incidence of precursor lesions and CRC between the different variants and treatment variation for CRC in LS. Results From a cohort of 621 LS individuals 496 (133 MLH1, 107 MSH2, 180 MSH6 and 76 PMS2) could be included in this study. Analyses revealed that, despite adequate surveillance intervals and lower adenoma incidence, individuals with a gPV in MLH1 or MSH2 have higher CRC incidences compared to MSH6 or PMS2. Most detected CRC lesions were early stage (T1) CRCs. Treatment for T1 CRC varied considerably; in 68% of the cases deviating from a subtotal colectomy, with nearly equivalent recurrence rates. Discussion Based on higher precursor lesion detection and lower CRC incidences in LS individuals with a gPV in MSH6 or PMS2 under biannual endoscopic surveillance, this study supports the potential for extended surveillance intervals in the latter group. As treatment for the detected T1 CRCs varied considerably with nearly equivalent recurrence rates, in selected cases less invasive interventions for LS individuals could be considered.